Nanostructure-based proton exchange membrane for fuel cell applications at high temperature - Li, Junsheng; Wang, Zhengbang; Li, Junrui; Pan, Mu; Tang, Haolin (Journal of nanoscience and nanotechnology, 2014)
As a clean and highly efficient energy source, the proton exchange membrane fuel cell (PEMFC) has been considered an ideal alternative to traditional fossil energy sources. Great efforts have been devoted to realizing the commercialization of the PEMFC in the past decade. To eliminate - some technical problems that are associated with the low-temperature operation (such as catalyst poisoning and poor water management), PEMFCs are usually operated at elevated temperatures (e.g., >100 °C). However, traditional proton exchange membrane (PEM) shows poor performance at - elevated temperature. To achieve a high-performance PEM for high temperature fuel cell applications, novel PEMs, which are based on nanostructures, have been developed recently. In this review, we discuss and summarize the methods for fabricating the nanostructure-based PEMs for PEMFC operated - at elevated temperatures and the high temperature performance of these PEMs. We also give an outlook on the rational design and development of the nanostructure-based PEMs.
Gesehen am 28.10.2020